Star wars, Episoed VI Return of the Jedi - Marquand, Richard; Lucas, George; Kasdan, Lawrence; Lucasfilm, Ltd.; Twentieth Century-Fox Film Corporation (Hollywood, Calif. Lucasfilm Ltd, 2000)
Darth Vader and the Empire are building a new, indestructible Death Star. Meanwhile, Han Solo has been imprisoned, and Luke Skywalker has sent R2D2 and C3PO to try and free him. Princess Leia, disguised as a bounty hunter, and Chewbacca go along as well. The final battle takes place on the moon of Endor, with its natural inhabitants, the Ewoks, lending a hand to the rebels.
Originally released as a motion picture in 1983.
Issued in a case with star wars, episode IV: a new hope and star wars ; episode V: the empire strikes.
Director of photography, Alan Hume ; editors, Sean Barton, Duwayne Dunham, Marcia Lucas ; music, John Williams ; costume designers, Aggie Guerard Rodgers, Nilo Rodis- Jamero ; production designer, Norman Reynolds ; visual effects, Richard Edlund, Dennis Muren, Ken Ralston, Nina Saxon.
Mark Hamill, Harrison Ford, Carrie Fisher, Billy Dee Williams, Anthony Daniels, Peter Mayhew, Sebastian Shaw, Ian McDiarmid, David Prowse, Alec Guinness.
MPAA rating: PG; for sci-fi action violence.
VCD
Keywords: Skywalker, Luke -- (Fictitious character) -- Drama; Vader, Darth -- (Fictitious character) -- Drama; Prisons -- Drama; Space warfare -- Drama